A Study Comparing the Risk of Adverse Pregnancy Outcomes in Women with and without Polycystic Ovarian Syndrome - Maria Ahmad Khan, Uzma Hasan, Syeda Husna, Abdur Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Methodology: Researchers at Nishter Hospital in Multan analysed data from 100 pregnant women who were enrolled in their antenatal care between the ages of 20 and 45. Fifty women were diagnosed with PCOS, while another 50 served as controls. Patients' demographic, clinical, menstrual, and pregnancy information was documented. We monitored maternal outcomes such as spontaneous abortion, GDM, preterm birth, and PIH from enrollment till delivery in all patients (PIH). SPSS Statistics 20.0 was the programme that was used for the statistical analysis. RESULTS: The majority of the participants (59%) were between the ages of 20 and 30. The percentage of women with PCOS who had a high body mass index (BMI) was significantly higher than that of the control group, which was 38 percent. GDM occurred in 10(20%) with PCOS and 7(14%) in cases without PCOS, p-value=0.42, PIH in PCOS was 11(22%) whereas in controls it was 9(18%), p-value=0.62, preterm birth was higher in cases with PCOS i.e. 13(26%) and in controls 6(12%), p-value=0.07), Spontaneous abortions (SAB) occurred in 5(10%) in PCOS and 2(4%) in without PCOS, vaginal delivery was higher in controls i.e. 37(74%) where in PCOS it was 21(42%), cesarean delivery was recorded in 11(22%) in controls while 24(48%) in cases with PCOS, p-value=0.005. Conclusion: PCOS pregnancy complications include SAB, GDM, and premature birth which were higher in PCOS group. Moreover, these pregnancies are at high-risk of pregnancy outcome and require frequent prenatal care. Keywords: PCOS, pregnancy outcome, antenatal care